The association between adverse pregnancy outcomes with genital Chlamydia Trachomatis infection among pre-pregnancy couples in Shenzhen, China: A cross-sectional study - Sun, Si; Zhang, Li; Wu, Qiuhong; Tian, Lishan; Ding, Yi; Liu, Lanlan; Ye, Hailing; Li, Bo; Luo, Zhenzhou (Frontiers in Public Health, 2022)
Objectives To investigate the prevalence of adverse pregnancy outcomes (APOs) in women and the impact of pre-pregnancy couples' genital Chlamydia Trachomatis (GCT) infection and other infections on APOs. Study design Data on genital infections were collected from the Free Pre-pregnancy Health Check (FPHC) in Shenzhen, China. Data on APOs were collected from a 1-year telephone follow-up of pregnancy status and subsequent pregnancy outcomes. Methods APO data were used to count adverse outcomes, and logistic regression was conducted to determine the association between APOs and GCT infection. Results From December 2018 to December 2019, among 4,429 couples who underwent FPHC; 1,925 were pregnant, and 1,816 couples were tracked for pregnancy outcomes, including 1,471 normal pregnancies and 345 (19.00%) APOs. The rest of 109 pregnant couples did not answer the phone or refused to answer the pregnancy outcome during the follow-up. Among APOs, the number of spontaneous abortions was 122 (35.36%), the number of macrosomia was 85 (24.64%), the number of low birth weight (LBW) & preterm births (PTB) was 39 (11.30%), the number of LBW was 34 (9.86%), and the number of PTB was 31 (8.99%). The prevalence of GCT infection in females and males was 4.24% [95% Confidence Interval, (CI): 3.41–5.27%] and 3.58% (95% CI: 2.79–4.57%), respectively. More than half (52.69%, 49/93) of the couples were GCT-concordant. The prevalence of APOs in couples without GCT infection was 18.74% (332/1,772). The prevalence of APOs in female GCT-discordant was 32.14% (9/28), and the prevalence of APOs in male GCT-discordant was 25% (4/16). The prevalence of APOs in GCT-concordant was 12.24% (6/49). Multivariable analysis indicated that females 30–35 years old [adjusted Odds Ratio (aOR) = 1.08, 95% CI: 1.01–1.17] and over 35 years old (aOR = 1.16, 95% CI: 1.03–1.32) were more likely to experiencing APOs. Conclusion Although only women's age was found to be associated with APOs, the prevalence of APOs with GCT-discordant in couples, especially female GCT-discordant, was higher than in those without infection or who were GCT-concordant, suggesting that these groups, especially in older women, should be paid more attention to in follow-ups to improve reproductive health.